2014
DOI: 10.1371/journal.pone.0093757
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity and Specificity of Using a Computer Aided Diagnosis Program for Automatically Scoring Chest X-Rays of Presumptive TB Patients Compared with Xpert MTB/RIF in Lusaka Zambia

Abstract: ObjectiveTo determine the sensitivity and specificity of a Computer Aided Diagnosis (CAD) program for scoring chest x-rays (CXRs) of presumptive tuberculosis (TB) patients compared to Xpert MTB/RIF (Xpert).MethodConsecutive presumptive TB patients with a cough of any duration were offered digital CXR, and opt out HIV testing. CXRs were electronically scored as normal (CAD score ≤60) or abnormal (CAD score>60) using a CAD program. All patients regardless of CAD score were requested to submit a spot sputum sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 29 publications
4
80
1
Order By: Relevance
“…A further development is application of computer-aided image analysis to provide an automated imaging service. Studies suggest that sensitivities from automated readers can be similar to those obtained by eye but that specificity is reduced [27], a finding confirmed by studies in Africa [28,29]. Alternative imaging technologies such as magnetic resonance imaging, computed tomography, and positron emission tomography-computed tomography (PET-CT) may eventually find utility in the investigation of extrapulmonary disease [26].…”
Section: Imagingmentioning
confidence: 86%
“…A further development is application of computer-aided image analysis to provide an automated imaging service. Studies suggest that sensitivities from automated readers can be similar to those obtained by eye but that specificity is reduced [27], a finding confirmed by studies in Africa [28,29]. Alternative imaging technologies such as magnetic resonance imaging, computed tomography, and positron emission tomography-computed tomography (PET-CT) may eventually find utility in the investigation of extrapulmonary disease [26].…”
Section: Imagingmentioning
confidence: 86%
“…In this regard, our methodology was similar to that in other studies examining interreader performance in diagnostic imaging with and without an intervention such as computer-aided diagnostic software. Parallel methodology has been used in lung disease, [39][40][41][42][43] breast imaging, 29,[44][45][46] and Alzheimer disease, 26,47 without determining intraobserver variability.…”
Section: 712mentioning
confidence: 99%
“…14,15 The software ran on the same computer that was used as the viewing station and analysed all images in the background autonomously after initial installation.…”
Section: X-ray Reading and Radiological Referencementioning
confidence: 99%
“…14 Breuninger et al compared it against culture (excluding non-tuberculous mycobacteria, clinically presumed culture-negative cases and extra-pulmonary TB), and reported an AUC of 0.84. 15 The performance of X-ray readers in identifying TB in CXRs was found to be highly variable, and although many studies report high sensitivity (sometimes up to 100%) 24 and low specificity, some authors found the specificity to be higher than the sensitivity.…”
Section: Public Health Action Cad4tb In Tanzanian Prisons 252mentioning
confidence: 99%
See 1 more Smart Citation